Pheromone receptors for japonilure in Anomala corpulenta and Popillia japonica - Yinliang Wang; Kun Feng; Haoqin Ke; Huanhuan Dong; Kebin Li; Bingzhong Ren; Chen Luo; Cheng Qu; Ran Wang; Jiao Yin; Walter S. Leal (Proceedings of the National Academy of Sciences, 2026)
Using gas chromatography-electroantennographic detection (GC-EAD), gas chromatography-mass spectrometry (GC-MS), and chiral capillary GC with synthetic stereoisomers, followed by laboratory and field validation, we identified the sex pheromone of the copper green chafer ( Anomala corpulenta ) as ( R )-japonilure, with its antipode, ( S )-japonilure, acting as a behavioral antagonist. Single sensillum recordings (SSR) revealed two types of pheromone-responsive sensilla, one narrowly tuned to the sex pheromone, and another that responded to both ( R )- and ( S )-japonilure, albeit with lower sensitivity to the latter. Functional characterization of A. corpulenta odorant receptors (ORs) by two-electrode voltage clamp (TEVC) led to the identification of two key receptors, AcorOR18, which was selective for ( R )-japonilure, and AcorOR29, which was activated by both enantiomers, and 10 ORs sensitive to plant-derived compounds. SSR combined with fluorescence in situ hybridization (FISH) experiments suggested that AcorOR18 is expressed in pheromone-specific sensilla, whereas AcorOR29 is localized in sensilla responsive to both the pheromone and its antagonist. RNA interference (RNAi) knockdown of either receptor reduced male attraction to ( R )-japonilure, while simultaneous knockdown of both genes abolished behavioral responses, confirming that both receptors are required for full pheromone detection. Three orthologous receptors were identified in the Japanese beetle ( Popillia japonica ) genome. Two of them, PjapOR42 and PjapOR37, exhibited strict enantioselectivity for ( R )-japonilure, whereas PjapOR39 showed a relaxed enantiospecificity, responding to both enantiomers and preferentially to the behavioral antagonist. These results suggest that PjapOR39 may mediate detection of ( S )-japonilure and contribute to behavioral antagonism, revealing a shared molecular mechanism of enantiomeric discrimination in scarab beetles.